Legal Pluralism in Qing China : Transplantation and Transformation - Wong, Max WL, (Asian Studies E-Books Online, Collection 2025., 2025)
In this book, Max WL Wong provides a new perspective on legal pluralism under the Qing dynasty (1644-1911) and provides an argument that in traditional Chinese legal culture the pluralistic normative orders were blended, in parallel with the established state legal system, to become a complexed administrative system exerting political and social control in Qing China. Specifically, he addresses these key questions. First, how were Chinese laws, and the quasi-legal norms that created a system of legal pluralism in Qing, reformed by the drive for legal modernization in the late Qing and Republican China as a response to the challenge of western laws? And second, how was the pluralistic structure of Chinese laws and norms in Qing China diffused and transplanted to Taiwan, Hong Kong and South East Asia in the form of 'Chinese customary law'? Also, how was Chinese law subdued by the imposed legal systems of the colonisers, mainly Great Britain and Japan? See Less